Creating Value from Mergers and Acquisitions / The Challenges: An Integrated and International Perspective - Sudarsanam Sudi (Prentice Hall, 2003)
This book provides a comparative analysis of the M & A scene in Europe and the US, the two most active markets in the World.
Preface, Publisher's Acknowledgements, Introduction, Historic and Conceptual and Performance Overview of Mergers and Acquisitions, Historical Overview of Mergers and Acquisitions Activity, Alternative Perspectives on Mergers, Are Acquisitions Successful?, Corporate Strategy and Organizing for Acquisitions, Sources and Limits of Value Creation in Horizontal Mergers, Sources and Limits of Value Creation in Consolidating Fragmented Industries, Sources and Limits of Value Creation in Vertical Mergers, Sources and Limits of Value Creation in Conglomerate Acquisitions, Cross-Border Acquisitions, Strategic Alliances as an Alternative to Mergers and Acquisitions, Corporate Refocusing, Leverage Buyouts, Organizing for Acquisitions, Deal Structuring and Negotiation, Target Valuation, Accounting for Mergers and Acquisitions, Paying for the Acquisition, Antitrust Regulation, Regulating Takeover Bids, Advisers in Takeovers, Post-Acquisition Integration and Organizational Learning, Index.